2013
DOI: 10.1128/jvi.01546-13
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Sequence Variation in the UL128 Locus on Production of Human Cytomegalovirus in Fibroblast and Epithelial Cells

Abstract: The human cytomegalovirus (HCMV) virion envelope contains a complex consisting of glycoproteins gH and gL plus proteins encoded by the UL128 locus (UL128L): pUL128, pUL130, and pUL131A. UL128L is necessary for efficient infection of myeloid, epithelial, and endothelial cells but limits replication in fibroblasts. Consequently, disrupting mutations in UL128L are rapidly selected when clinical isolates are cultured in fibroblasts. In contrast, bacterial artificial chromosome (BAC)-cloned strains TB40-BAC4, FIX, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
116
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(128 citation statements)
references
References 82 publications
10
116
1
Order By: Relevance
“…Importantly, despite the overall small amount of gH/gL in ME, the amount of gH/gL/UL128-131 was dramatically more than was detected in TB or TR virions. While the HCMV virions analyzed here were produced in fibroblasts, Murrell et al produced virions in epithelial cells and found that TR contained amounts of gH/gL/ UL128-131 comparable to those in ME and that TB had noticeably less (59). These discrepancies suggest that factors of the host cell type might influence the assembly of HCMV gH/gL complexes.…”
Section: Discussionmentioning
confidence: 48%
“…Importantly, despite the overall small amount of gH/gL in ME, the amount of gH/gL/UL128-131 was dramatically more than was detected in TB or TR virions. While the HCMV virions analyzed here were produced in fibroblasts, Murrell et al produced virions in epithelial cells and found that TR contained amounts of gH/gL/ UL128-131 comparable to those in ME and that TB had noticeably less (59). These discrepancies suggest that factors of the host cell type might influence the assembly of HCMV gH/gL complexes.…”
Section: Discussionmentioning
confidence: 48%
“…Zhou et al demonstrated that the amount of these two complexes in the virion envelope varies dramatically among different strains of HCMV (17). This may be partly explained by the findings of Murrell et al indicating that nucleotide polymorphisms within the UL128-131 locus affect mRNA splicing and, thus, the amounts of the proteins available for assembly of the gH/gL/UL128-131 complex (18). Another factor may be the UL148 protein, which was recently characterized by Li et al as an endoplasmic reticulum (ER) resident protein that influences the assembly of gH/gL/gO and gH/gL/UL128-131 (19).…”
mentioning
confidence: 84%
“…We suggest, however, that because trimer accounts for most of the gH/gL on TB40/E virions (17), a decrease in overall virion levels of gH/gL might be expected when a factor important for its efficient maturation is absent. In addition, TB40/E contains a mutation in intron 1 of UL128 that causes inefficient splicing of UL128 transcripts and hence, inefficient expression of the pentamer (11). Therefore, a strain-specific bottleneck in UL128 expression may have prevented an increase in pentamer levels from occurring when UL148 was disrupted.…”
mentioning
confidence: 99%
“…It is now established that the pentameric complex is required for infection of epithelial cells and endothelial cells. During adaptation to culture in fibroblasts, natural isolates of HCMV quickly accumulate mutations in UL128, UL130, or UL131 that either prevent maturation of the pentamer or substantially diminish its expression on virions (10,11). Therefore, most laboratory-adapted HCMV strains express only gH/gL/gO (trimer).…”
mentioning
confidence: 99%